The Steps of Logo Design at Kastamonu University, Forestry Faculty - Sakici, Cigdem; Ayan, Elif (Elsevier BV, 2012)
AbstractLogo is symbolizing a firm, product or the name of a service by using letter and image elements. Logo should not reflect designer logo should reflect the firm or product's properties. Selected or designed font should be suitable with the content of institution, hi addition to this; knowing how the firm defines itself and its concept are important stages for the logo design. The logo should be; simple, easily understandable, rememberable and original. It should neither be mixed with other firms’ logos nor even remind them. Hence; for the Kastamonu University Forestry Faculty's logo design, creating the appropriate logo was aimed. Because of this aim sketches, taking into consideration dominant features of Faculty, University and Kastamonu, were made by expert group of 5 person who has a enough knowledge for designing elements and principles. Suggestions were made 42 item. Suggestions were gotten pre-elimination by Landscape Architecture Faculty Staffs (jure)- After that, 30 sketches shared in user groups one to one and via e-mail in order to determine the percentage of preferation. They were asked to 3 choice of the most admired of these options and to comment on their favorite choice. Finally, results was evaluated by the same jure and was determinate 5 sketches that most voted. Having regard to the sketches, people who make up these alternative logos, developed the design again and they gave the final shape with using design principles and elements for the logo. 5 logo resent to user group. As a final evaluation, idea for leaving a trace on minds between Turkey's Forest Faculties and World's Forest Faculties, most suitable logo was selected for our faculty's identity.
Keywords: Corporate Identity; Brand; Logos; 4. Education; 15. Life on land